Optimisation of Doped Antimony Sulphide (Sb2S3) Thin Films for Enhanced Device Applications - P.A.В Nwofe; J.N. Chukwu (Журнал нано- та електронної фізики)
Energy scarcity is ubiquitous, and more acute in developing nations. Diversification of energy sources toward renewable energy is one of the world major approach in solving this problem. Thin film solar cells is universally recognized as one of the best way forward, thus investigation of low cost, non toxic inorganic materials for use in absorber and window layers in thin film photovoltaic solar cell devices will play a significant role in that regard. Thin films of antimony sulphide were grown using the solution growth technique. The films were doped with nickel impurities and annealed at annealing temperatures in the range 50В В°C to 200В В°C, with the annealing time fixed for 1 hour. The films were characterised using X-ray diffractometry to investigate the structural properties and UV-spectroscopy to investigate the optical properties, thus enabling to evaluate the optical constants (optical absorption coefficient, energy bandgap, refractive index, extinction coefficient, optical density, dielectric constants etc). The results from the structural analysis indicate that the films are mostly amorphous, and exhibited a polycrystalline form at an annealing temperature of 150В В°C. The optical analysis show that the optical absorption coefficient were пЂѕВ 104В cmВ вЂ“В 1, the energy bandgap was direct with values in the range 2.26В eV to 2.52В eV. The results of the optical studies (direct energy bandgap, values of the energy bandgap and low resistivity) indicate that the films will be utilised as window layers in solar cell devices and in other optoelectronic applications.